2023
DOI: 10.3390/plants12122386
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Foliar Supplementation of Silicon on Physiological and Biochemical Responses of Winter Wheat to Drought Stress during Different Growth Stages

Abstract: Drought is one of the major environmental stresses, resulting in serious yield reductions in wheat production. Silicon (Si) has been considered beneficial to enhancing wheat resistance to drought stress. However, few studies have explored the mediated effects of foliar supplementation of Si on drought stress imposed at different wheat growth stages. Therefore, a field experiment was carried out to investigate the effects of Si supplementation on the physiological and biochemical responses of wheat to drought s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Following inoculation, these enzymes were upregulated in the susceptible cultivars, whereas CAT and POX activities were noticeably elevated in the resistant cultivars. Under several stressors, these enzymes play a vital role in reducing ROS levels or scavenging to detoxify and remove their harmful effects [42][43][44][45][46]. Also, the increase in electrolyte leakage may be due to the effect of the pathogen on the cell membrane in the susceptible cultivars (Misr-1 and Misr-2) and its permeability, whereas the membrane permeability of the resistant cultivars (Misr-3 and Sakha-95) were not affected under infection.…”
Section: Discussionmentioning
confidence: 99%
“…Following inoculation, these enzymes were upregulated in the susceptible cultivars, whereas CAT and POX activities were noticeably elevated in the resistant cultivars. Under several stressors, these enzymes play a vital role in reducing ROS levels or scavenging to detoxify and remove their harmful effects [42][43][44][45][46]. Also, the increase in electrolyte leakage may be due to the effect of the pathogen on the cell membrane in the susceptible cultivars (Misr-1 and Misr-2) and its permeability, whereas the membrane permeability of the resistant cultivars (Misr-3 and Sakha-95) were not affected under infection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with exogenous applications of these components and by targeting the most water-sensitive growth stages, the negative impacts of DI stress on wheat growth and production can be effectively minimized. However, previous studies have shown that although water deficit stress affects the growth and productivity of wheat at different growth stages, the efficiency of the exogenous application of these components in alleviating this stress varies with different growth stages [ 19 , 43 ]. For instance, Ning et al [ 43 ] reported that the foliar application of silicon (Si) to wheat crops during the reproductive stage was more effective in mitigating the adverse effects of drought stress on physiological traits and grain yield as opposed to applying it during the jointing stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have shown that although water deficit stress affects the growth and productivity of wheat at different growth stages, the efficiency of the exogenous application of these components in alleviating this stress varies with different growth stages [ 19 , 43 ]. For instance, Ning et al [ 43 ] reported that the foliar application of silicon (Si) to wheat crops during the reproductive stage was more effective in mitigating the adverse effects of drought stress on physiological traits and grain yield as opposed to applying it during the jointing stage. Gong et al [ 44 ] found that the foliar application of Si is more effective in enhancing wheat defense against oxidative stress during drought when applied at the grain filling stage, with minimal impact when applied at the booting stage.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of wheat occurs within diverse farming systems, with production management practices being influenced by a range of agro-climatic factors, including temperature, rainfall, day length, soil type, and topography, as well as biotic and socioeconomic factors [ 5 ]. However, changes in precipitation patterns, due to natural or anthropogenic effects, are triggering yield damage, particularly in arid areas [ 6 , 7 ]. Drought, as one of the most common abiotic stresses on plants in these areas, results in global yield losses of 20% for wheat [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%